Associations of physical activity and sedentary behavior during pregnancy with gestational diabetes mellitus among Asian women in Singapore - Natarajan Padmapriya; Jonathan Y. Bernard; Shen Liang; See Ling Loy; Shirong Cai; Iris Shen Zhe; Kenneth Kwek; Keith M. Godfrey; Peter D. Gluckman; Seang Mei Saw; Yap-Seng Chong; Jerry Kok Yen Chan; et al. (BMC, 2017)
Abstract Background Few studies have investigated physical activity (PA) and sedentary behavior (SB) in relation to fasting (FG) and 2-h postprandial plasma glucose (2hPG) levels and gestational diabetes mellitus (GDM); we investigated these associations among Asian pregnant women. Methods As part of the Growing Up in Singapore Towards healthy Outcomes cohort study, PA and SB (sitting and television times) were assessed by interviewer-administered questionnaire. During 75 g oral glucose tolerance tests at 26-28 weeks' gestation we measured FG, 2hPG levels and GDM (FG ≥ 7.0 mmol/L and/or 2hPG ≥ 7.8 mmol/L). Associations were analysed by multiple linear and logistic regression. Results Among the 1083 women studied, 18.6% had GDM. SB was not associated with FG, 2hPG and GDM. Higher categories of PA were associated with lower 2hPG and a lower likelihood of GDM (p-trend < 0.05), but not with FG levels. Compared to insufficiently active women, highly active women had lower 2hPG levels [β (95% CI): -0.32 (−0.59, −0.05), p = 0.020) and were less likely to have GDM [OR: 0.56 (0.32-0.98), p = 0.040]. Stratified analysis revealed no associations among under/normal-weight women, but significant associations among overweight/obese women; in those with BMI ≥23 kg/m2, sufficiently active and highly active women were less likely to have GDM [OR: 0.52, (0.29-0.93), p = 0.028, and OR: 0.34, (0.15-0.77), p = 0.010, respectively]. Conclusion Higher PA was associated with lower 2hPG levels and a lower prevalence of GDM, particularly in overweight/obese women. Further studies are warranted to confirm these findings, and to examine the effectiveness of PA promotion strategies for the prevention of gestational hyperglycemia.